2020
DOI: 10.1007/978-3-030-55115-5_42
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Vulnerability Assessment of City Regions Based on Building Typology

Abstract: Over half of India's territory zone is prone to seismic tremors, and the Indian subcontinent has encountered many earthquakes in the past. This study focuses on the vulnerability assessment of buildings by Rapid Visual Screening (RVS) in selected regions of Tier II city of south India-Coimbatore. The building typologies present in various city regions (normally designated as Corporation wards) and potential seismic vulnerability of buildings in each city region (ward) is determined by RVS methodology. The RVS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study concluded that the use of steel jacketing can improve the compressive strength and flexural study of the columns. RVS was done by [66] to assess vulnerability in the city of Coimbatore and concluded that building present were vulnerable and hence required retrofitting.…”
Section: Tier 3: Detailed Evaluation Phasementioning
confidence: 99%
“…The study concluded that the use of steel jacketing can improve the compressive strength and flexural study of the columns. RVS was done by [66] to assess vulnerability in the city of Coimbatore and concluded that building present were vulnerable and hence required retrofitting.…”
Section: Tier 3: Detailed Evaluation Phasementioning
confidence: 99%